2022
DOI: 10.1097/01.hs9.0000843980.18213.bf
|View full text |Cite
|
Sign up to set email alerts
|

S272: Safety and Preliminary Pharmacodynamic Effects of the Ferroportin Inhibitor Vamifeport (Vit-2763) in Patients With Non-Transfusion-Dependent Beta Thalassemia (Ntdt): Results From a Phase 2a Study

Abstract: Background:Background: NTDT is characterized by an imbalanced α /β -globin chain ratio, ineffective erythropoiesis, increased intestinal iron absorption and iron overload. Vamifeport inhibits ferroportin-mediated iron export into plasma and has been shown to decrease serum iron and transferrin saturation (TSAT) levels in relevant animal disease models and healthy volunteers. Aims:Aims: The primary objective of this multicenter, Phase 2a, double-blind, randomized, placebo-controlled study (NCT04364269) was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Vamifeport reduced serum iron and TSAT levels in healthy volunteers 28 and more recently has been shown to reduce serum iron and TSAT levels in patients with non-transfusion-dependent β-thalassemia. 29 In addition to β-thalassemia, vamifeport has been shown to correct ineffective erythropoiesis and to ameliorate abnormal myelopoiesis in a mouse model of myelodysplastic syndrome. 30 Moreover, vamifeport prevented further liver iron overload in a mouse model of hereditary hemochromatosis, 31 improved hemodynamics in a mouse model of sickle cell disease, 15 and corrected hematocrit and RBC levels in a mouse model of polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
“…Vamifeport reduced serum iron and TSAT levels in healthy volunteers 28 and more recently has been shown to reduce serum iron and TSAT levels in patients with non-transfusion-dependent β-thalassemia. 29 In addition to β-thalassemia, vamifeport has been shown to correct ineffective erythropoiesis and to ameliorate abnormal myelopoiesis in a mouse model of myelodysplastic syndrome. 30 Moreover, vamifeport prevented further liver iron overload in a mouse model of hereditary hemochromatosis, 31 improved hemodynamics in a mouse model of sickle cell disease, 15 and corrected hematocrit and RBC levels in a mouse model of polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
“…29-31 32 However, clinical studies on iron restriction in TDT or NTDT subjects were either unsuccessful or terminated early (Table 3S). 33,34 Bitopertin, a glycine transport inhibitor that reduces heme synthesis (Figure 2) had a similar fate. Bitopertin was expected to re-balance heme and globin synthesis and to reduce erythroid oxidation.…”
Section: Molecules Targeting Iron-homeostasis or Heme Synthesismentioning
confidence: 91%
“…Hepcidin mimetics, stimulators of its production and ferroportin inhibitors have seen early clinical stage testing as to their safety and potential efficacy [ 106 ]. The ferroportin inhibitor VIT-2763 has advanced to phase II trials and it has shown both low toxicity and good potential for lowering serum iron levels [ 107 ] Other approaches of using hepcidin mimetics including PTG-300 (rusfertide) have shown promising phase III results. As of yet, none of these have received regulatory approval for ongoing clinical use [ 108 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%